Bioconcentration and translocation of rare earth elements in plants collected from three legacy mine sites in Portugal - Forsyth, Kaisa; Dia, Aline; Marques, Rosa; Prudêncio, Maria Isabel; Diamantino, Catarina; Carvalho, Edgar; Russo, Dulce; Dionisio, Isabel; Davranche, Melanie; Bouhnik-Le-Coz, Martine; Pédrot, Mathieu (Frontiers in Environmental Science, 2023)
This field study aims to evaluate the phytoavailability and fate of rare earth elements (REE), a group of emerging contaminants. Spontaneous vegetation and related media (soils and surface waters) were collected from three Portuguese legacy mine sites in November 2020. Though none of the studied mines targeted the extraction of REE ores, the prevailing geochemistry of the mining environment favors their mobility, and is therefore ideal for demonstrating the behavior, fate, and cycling of REE in the environment. Data were analyzed in the context of the (i) prevailing geochemical context, (ii) the mining context, and (iii) plant effects. This study presented the REE signatures for different plant species and linked the signatures to a potential source of bioavailable REE. The REE accumulated in plant tissue seemed to reflect the REE signature of surface waters in the mining areas, showing enrichment in middle REE. Although the soils, sediments, and waters in this study had similar features, certain plants seemed better adapted to extracting particular REE over others. Light REE and Eu in particular seemed to be accumulating and translocating more, depending on plant type. This is of interest because REE share many physical and chemical characteristics and have thus been used as accurate tracers of various environmental samples. Given that REE are readily available within the field conditions of a mining site, this study shows how plant physiology and biologic preference towards particular REE contributes to the fractionation of REE and creates a unique signature dependent on plant type.